Pre-service Teachers’ Use of ICT in Saudi Education: Literature Review - Alshammari, Yousef; Alharbi, Omran; AlMutairi, Awatif (Advances in Social Sciences Research Journal, 2022)
Various technological tools are commonly used in education, due to rapid advances in the Information and Communications Technology (ICT) field. In recent years several institutions and schools in Saudi Arabia have started using ICT in the classroom. The purpose of this review is to assess the available literature to establish the extent of pre-service teachers’ understanding of ICT and the level of ICT use in Saudi education, over the last decade. The findings show that pre-service teachers seem to lack the necessary level of technical knowledge to use ICT effectively in the classroom. The results also revealed several obstacles to the use of ICT in education, including a lack of training, a shortage of resources, and insufficient clarity of the Ministry of Education’s policy regarding using ICT in teaching. In light of these findings, thia study suggests that the Saudi educational environment be adapted and improved to make the adoption and use of ICT more successful. It also suggested that pre-service teachers receive training both at university and when they reach their schools on how to incorporate ICT successfully into their teaching and learning practice.